Características tipológicas dos produtores de leite do município de Leopoldina, Minas Gerais - Fernandes de Araújo, José Geraldo; Seabra Rocha, Dilson; Machado Filho, Francisco; Ribon, Miguel; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
This study analyzes the characteristics of milk producers as well as identifying those most important in influencing the adoption of new practices in the município (county) of Leopoldina, Minas Gerais.